A semantically-based approach to teaching verbs in English. - Fiallo Alonso del Rivero, Pedro Alberto (2023)
The research carried out aimed at finding out whether the semantic description of the verbal lexeme provides the necessary characteristics to determine the rightful use of the verbal lexeme in English language. Qualitative approach allowed for the analysis of the selected corpus. The descriptive research focused on the verb as the main unit of predication for its classification and semantic description. Corpus linguistics was used to retrieve the verbal lexemes from the online Merriam-Webster’s dictionary 2023. Several criteria were established to characterize the lexico-semantic variants which resulted from componential analysis, and a matrix was designed, based on previously matrixes by researchers in the field, to analyze the presence or absence of the features previously determined. The results showed that through the analysis of the lexico-semantic variants that make up the verbal lexeme, it was possible to determine what characteristics appear or not, allowing for specific combinability of each lexeme, as meaning is actualized through the different uses of each one of them. The conclusions arrived at show that the detailed characterization of verbs can help users determine what lexico-semantic variant to use based on the actual context, rather than on the partners the lexeme is to take.